Pengembangan Sentra Produksi Kemasan Berbasis Anyaman Bambu Melalui Pemberdayaan Karang Taruna dan PKK untuk Peningkatan Ekonomi Masyarakat di Desa Mojorejo Kecamatan Jetis Kabupaten Ponorogo - Mohammad Muslih; Use Etica; Eka Rosanti; Ely Windarti Hastuti; Wildan Mubarok (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
As an agricultural-based village, wives in Mojorejo village located in Ponorogo, East Java have been supporting the family income from occasional production of bamboo handicrafts, e.g., ‘besek’, ‘tumbu’, and ‘rinjing’ for generations. Despite its great potential, this bamboo handicraft is still produced individually with one family produced only one type of product, resulting in low economical impact for the family and the village. This community service program aimed to establish a ‘bamboo handicraft center’ with the final goal of increasing the income of the community in Mojorejo Village. This community service program employs a participatory rural appraisal (PRA) approach, which in the implementation of the program, several methods were used, in the form of focus group discussions, training, technology introduction, counseling, and mentoring. As a result of this community development program, the community's economy has increased through the development of new products and management of the micro-businesses from production to marketing